Comparative Study Of Learning Achievement Using The Structured Handouts - Listiadi, Agung (International Journal of Educational Research & Social Sciences, 2022)
The learning achievement of each student will not be the same, because each student has certain abilities that vary from other students in terms of ability and ability to master the material, even though the object/criteria for the assessment are the same. For this reason, study Structured handouts that are in accordance with the characteristics of students are very supportive in improving study achievement. Structured handouts are basically self-instruction. Therefore, study through structured handouts emphasizes the active role of students in study themselves. This study uses a quantitative Independent T test method by comparing the mean of the control class and the experimental class. The results of the Independent t test showed that the calculated value resulted in an alpha significance value of less than α = 5%. Thus, it can be concluded that there is a significant difference in learning achievement before and after using the combined excel structured handout. The use of structured handouts in learning is more feasible in realizing creativity and innovation in students because it focuses on the individual abilities of students. Learning by using structured handouts allows students to measure their own abilities and can improve their own abilities without feeling pressured.